Potensi Produk Unggulan Daerah dan Strategi Pengembangannya di Kabupaten Kepulauan Aru - Eka Setiajatnika; Yudith Dwi Astuti (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
This study aims to identify the potential of rural superior products in the Aru Islands Regency and strategies for developing these rural superior products. This study uses a combination method (mixed methods). A quantitative approach was used to: (1) determine the regional superior products in the Aru Islands Regency which were analyzed by MRP analysis, study area growth (RPS), shift share analysis, location quotient (LQ) analysis, overlay, and classification typology; (2) determining the strategy of developing superior products for the Aru Islands Regency using the SWOT analysis method. The results showed that the determination of regional superior products using a hierarchical assessment of various aspects were: skills, raw materials, capital, production facilities and infrastructure, technology, socio-culture, management, markets, prices, employment, and roles in the economy. Identification of the potential of regional superior products using the analytical hierarchy process shows that the superior products of rural Aru Islands Regency are corn, mackerel, grouper, white snapper, sweet potato, beef, goat, mangrove crab, and seaweed. The strategies for developing rural superior products include: 1) Increasing the attractiveness of the quality of regional superior products; 2) Improving the quality of infrastructure (production); 3) Improving the quality of infrastructure (general); 4) Improving the quality of promotion and investment; 5) Increased cooperation; 6) Increasing community participation; and 7) Increased protection of Regional Superior Products.